Acute and long-term (2-years) clinical outcomes of the CoreValve 31 mm in large aortic annuli: A multicenter study. (15th January 2017) - Attizzani, Guilherme F.; Ohno, Yohei; Latib, Azeem; Petronio, Anna Sonia; Giannini, Cristina; Ettori, Federica; Curello, Salvatore; Bedogni, Francesco; Todaro, Denise; Brambilla, Nedy; Bruschi, Giuseppe; Colombo, Paola; et al.
Abstract: Introduction: Little is known about the early and late performance of the 31 mm CoreValve Revalving System (CRS, Medtronic Inc., Galway, Ireland). Our aim was to compare acute and long-term results of the 31 mm CRS with other valve sizes. Methods: Consecutive patients undergoing transcatheter aortic valve implantation (TAVI) with CRS in nine Italian centers were prospectively included and dichotomized according to prosthesis size in two different groups, as follows: 31 mm and other valve sizes (i.e., 23, 26, and 29 mm combined). End points were defined according to Valve Academic Research Consortium definitions. Propensity score matching was performed. Results: In total, 2069 patients (n = 169 [8%] in the 31 mm group and n = 1900 [92%] in the other valve sizes group) were included. After propensity matching, the implantation of the 31 mm valve was associated with lower rates of procedural- (91.3% vs. 98.1%, p = 0.030) and device-success (88.5% vs. 97.1%, p = 0.016), longer procedural time (120 [80–180] min. vs. 90 [60–120] min., p < 0.001), and higher rates of implantation of a second valve (10.6% vs. 2.9%, respectively, p = 0.027). The rates of permanent pacemaker implantation in the 31 mm group were higher but not statistically different from other valve sizes (41.7% vs. 30.9%, respectively, p = 0.149). Significant improvement, without between-group differences, was observed in NYHA functional class. Cardiovascular death was lower in the 31 mm valve group through 2-years (3.8% vs. 13.5%, respectively, p = 0.014). Conclusions: The acute performance of the 31 mm CRS was worse than other valve sizes but no negative impact was observed in long-term outcomes.